Probabilidade aplicada aos jogos de azar - Andrade, Rafael Thé Bonifácio de (2017)
Games are present in all phases of human life and some of them are considered game of chance. Game theory is a branch of mathematics concerned in decision models where the goal is to gain, and is applicable to several behavioral studies including economics, political science, psychology, and logic. The games studied in this theory have well de ned elements such as players, information and actions. In this work we will see that games of chance are games that are more likely to be defeated than win, we will deal with some well known and common games such as: Poker, Blackjack, Craps, Roulette and Lottery as the Mega-Sena. Show how these games work, their stories and the odds of a player to be successful in playing, in order to show mathematically the real chances of winning when playing these famous games.